Effects of financing on the type of innovation: An analysis for the Ecuadorian case - Londoño Espinosa, Sebastián; Andrade Suárez, Dennys (mktDESCUBRE; Vol 1 No 14 (2019): Fourteenth Edition (July - December), 2019)
Financing is one of the main constraints to innovation and has been a subject of great debate. The present investigation seeks to identify for the Ecuadorian case under empirical evidence the effect of financing on the type of innovation (in processes or products concatenated to the level of innovation, whether incremental or radical). The National Survey of Innovation Activities (ENAI) 2012-2014 is used as the main source. Using the multivariate probit and probit methodology, some relevant considerations were obtained: financing through the private sector is the one with the most statistical significance, financing with resources external and own have significant effects but not in the same magnitude to private financing; Finally, public financing or government support, together with the other types of financing, are not presented in any model as significant.